Perancangan Kampung Tematik Sawah dan Burung Hantu Menjadi Kawasan Wisata - Pratama, Raka Andika; Pangaribuan, Marcellino Sinar Hutama; Basuki, Yudi (Badan Riset dan Inovasi Daerah Kota Semarang, 2022)
The Thematic village is one of the flagship programs, which is a priority program for the Semarang City government. The existence of thematic villages is one of the tourist destinations in Semarang. The development of thematic villages to become tourist destinations is in line with one of the visions and missions of the development of the City of Semarang in 2021–2026. In addition, the development of thematic village areas is a form of adaptation by the Semarang City government to revive the tourism sector, which has been on hiatus due to the COVID-19 pandemic. One of the objectives of the development of thematic villages is to increase the potential of a competitive local economy and stimulate industrial development based on research and innovation based on the principles of Pancasila economic democracy. The mission was then followed up by organizing a priority program, namely